Bending-bearing behaviour of embedded steel ring-foundation connection of onshore wind turbines. (December 2021) - Amponsah, Evans; Wang, Zhenyu; Kwame Mantey, Selase
Highlights: Tests on small-scale specimens of the tower-foundation connection of onshore wind turbine are conducted. 3D non-linear numerical model of a large-diameter embedded steel ring to foundation connection is developed and analysed. The load-bearing behaviour of the embedded steel ring to foundation connection is sensitive to the embedment depth of the steel ring. Analytical model to predict the ultimate moment capacity of the embedded steel ring to foundation connection is proposed. Abstract: Embedded steel ring (ESR)–foundation connections are widely used in onshore wind turbines (WTs) to transfer the loads from the tower to the foundation. The load-bearing behaviour of the ESR–foundation connection greatly impacts on the structural integrity of onshore WTs under ultimate loads. The complex geometry, load-bearing mechanism and composite behaviour of the ESR–foundation connection present significant challenges for the optimal design of the connection. This paper proposes analytical equations to estimate the ultimate moment capacity of the ESR–foundation connection of onshore WTs. The load-bearing behaviour of the ESR–foundation connection was investigated through experiments on a small–scale model and numerical simulation on a large–scale model of the connection. A series of parametric studies were conducted to investigate the impact of key design parameters on the load-bearing behaviour of the ESR–foundation connection. The ultimate moment capacity, uplift resistance and extent of damage to the foundation were evaluated with respect to each parameter. The embedment depth of the steel ring was found to be the most significant parameter that impacts on the load-bearing behaviour of the ESR–foundation connection. About 90% of the bending loads are borne by the base flange-concrete and ESR wall–concrete contact surfaces. Based on the observed stress distributions and failure modes under ultimate loads, analytical expressions were proposed to estimate the ultimate moment capacity of the ESR-foundation connection.